Valor nutricional da silagem de Cynodon cv. Jiggs com adição de coprodutos do biodiesel - Azambuja, Guilherme Gostinhak (2018)
The aimed to evaluate the use of canola meal and cotton seed cake as additives in the nutritional composition and parameters of in vitro ruminal kinetics of Cynodon ssp. cv. Jiggs. The experiment was conducted in the municipality of Dois VizinhosPR. The Jiggs grass is established since the year 2016, in private property, located in the district of São Valentin, in the interior of the municipality. The experimental design was completely randomized, in a 2 x 5 factorial scheme, with six repetitions. The treatments corresponded to 5 levels of inclusion of two additives in silage: exclusive silage of Cynodon cv. Jiggs or addition of 6, 12, 18 and 28% of canola meal or cotton seed cake. The grass was processed and mixed to the additives according to the inclusion level, based on the estimated dry matter content. The material was ensiled on PVC microsilos of approximately 310cm3. After 60 days, the silos were opened. Were determined: pH, buffer capacity, gas and effluent losses, dry matter, mineral and organic matter, crude protein and its fractions, total carbohydrates and their fractions, in vitro digestibility of dry matter and total digestible nutrients. The data were submitted to analysis of variance and, in the case of a significant effect of the qualitative factor, the F test was used to compare the means (P=0.05). For the quantitative effect or interaction between the treatment factors, polynomial regression was performed (P=0.05). The addition of bran increased crude protein levels and soluble fractions. The fractions of the carbohydrates, both soluble and total, were reduced in quantity, without any damage to the silage conservation or the amount of total digestible nutrients.